Innateness as Closed Process Invariance. - Mallon, Ron; Weinberg, Jonathan M. (Philosophy of Science, 2006)
Controversies over the innateness of cognitive structures play a persistent role in driving research in philosophy as well as cognitive science, but the appropriate way to understand the category of the innate remains in dispute. The invariantist approaches of Stich and Sober face counterexample cases of traits that, though developing invariantly across different environments, nonetheless are not held by nativism partisans to count as innate. Appeals to canalization (Ariew) or to psychological primitiveness (Samuels) fail to handle this liberalism problem. We suggest a novel approach to innateness: closed process invariantism.